2019
DOI: 10.1038/s41598-019-41184-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electronic properties of magnetite across the high pressure anomaly

Abstract: The magnetite Fe3O4, being anciently known magnetic material to human kind and remaining in leading positions for development of advanced technologies presently, demonstrates a number of puzzling physical phenomena, being at focus of extensive research for more than century. Recently the pressure-induced anomalous behavior of physical properties of magnetite in vicinity of the structural phase transition, occurring at P ~ 25–30 GPa, has attracted particular attention, and its nature remains unclear. Here we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…The systems, where it can be observed, include single crystals [4][5][6][7] , thin films 8 , non-organic and organic molecules [9][10][11] , and even biomolecules [12][13][14][15] . The JTE approach is used for description of properties of functional materials, such as semiconductors [16][17][18] , magnetic materials 5,6,[19][20][21] , superconductors 22 , optical materials 10,18 , and multiferroics 4,17,23,24 . In crystals, the JTE can manifest itself local or uniform.…”
mentioning
confidence: 99%
“…The systems, where it can be observed, include single crystals [4][5][6][7] , thin films 8 , non-organic and organic molecules [9][10][11] , and even biomolecules [12][13][14][15] . The JTE approach is used for description of properties of functional materials, such as semiconductors [16][17][18] , magnetic materials 5,6,[19][20][21] , superconductors 22 , optical materials 10,18 , and multiferroics 4,17,23,24 . In crystals, the JTE can manifest itself local or uniform.…”
mentioning
confidence: 99%
“…This fraction could then be used for recycling metals, or it might find application as an oxygen carrier. Among the various Fe-bearing phases obtained through equilibrium calculations (Fe, FeO, olivine, hematite, and Fe-spinel), only Fe and Fe-spinel exhibit magnetic properties that could be exploited for separation at room temperature . The formation of Fe-spinel was calculated to occur in significantly higher concentrations under oxidizing conditions than metallic Fe was calculated to form under reducing conditions. This suggests that if magnetic separation is utilized the particles can be extracted in their oxidized state, which means that extraction should be performed after the combustor.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that a pressure of 5 GPa occurs at a depth of 160 km, where the temperature is approximately 1073 K (30). Although this value is slightly higher than the T c of the compressed sample at an ordinary pressure, it is reported that the T c of magnetite increases with pressure (31,32). Therefore, we predict that the compressed sample shows the ferromagnetism at 5 GPa and 1073 K. On the basis of these findings, we suggest that some compressed IH mineral series at depths in the upper mantle contribute to in situ Earth's magnetic anomalies.…”
Section: Discussionmentioning
confidence: 98%